Generation of a Reduced, Representative, Virtual Test Drive for Fast Evaluation of Tire Wear by Clustering of Driving Data - Muth, Lars; Noll, Christian; Sextro, Walter (Advances in Dynamics of Vehicles on Roads and Tracks II - Proceedings of the 27th Symposium of the International Association of Vehicle System Dynamics, IAVSD 2021)
Tire and road wear are a major source of emissions of nonexhaust particulate matter (PM) and make up the largest share of microplastics in the environment. To reduce tire wear through numerical optimization of a vehicle's suspension system, fast simulations of the representative usage of a vehicle are needed. Therefore, this contribution evaluates if instead of a full simulation of a representative test drive, only specific driving maneuvers resulting from a clustering of the driving data can be used to predict tire wear. As a measure for tire wear, the friction work between tire and road is calculated. It is shown that enough clusters result in negligible deviations between the total friction work of the full simulation and the cluster simulations as well as between the distributions of the friction work over the tire width. The calculation time can be reduced to about 1% of the full simulation.
Keywords: Tire Wear; Vehicle Dynamics; Clustering; Virtual Test

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

Development of an innovative separation unit for nitrogen recovery from agricultural waste - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny
Keywords: CFD; simulation; agricultural waste; multiphase

Maßnahmen zur Reduzierung von plastischer Verformung an statischen Druckplatten von Lammellenbremsen infolge einseitig eingebrachter hoher Reibleistung - Schadomsky, Magnus; Blumenthal, Lars Martin; Zimmer, Detmar; Peter, Simon; Boros, Laszlo (Forschung im Ingenieurwesen)
Die thermisch verursachte, plastische Verformung an statischen Druckplatten von Lamellenbremsen kann das Betriebsverhalten von Bremsen nachhaltig stören und sollte daher vermieden werden. So kann die plastische Verformung der Druckplatte beispielsweise zu einer Verkleinerung des Luftspalts führen und ungewollte Veränderung der Reibverhältnisse verursachen. Während des Bremsvorgangs dehnen sich hoch erwärmte Bereiche nah der Reibfläche aus und werden von den Zonen geringerer Temperatur an ihrer Ausdehnung gehindert. Überschreiten die daraus resultierenden Spannungen die Dehngrenze des Materials, kommt es zu plastischer Verformung. Dieser Artikel erläutert den physikalischen Verformungsprozess detailliert und darauf aufbauend, welche Maßnahmen zu einer Verringerung der Verformung ergriffen werden können. Dazu werden im Rahmen theoretischer Vorüberlegungen drei Ansätze identifiziert, die sowohl die Geometrie als auch die Werkstoffe der Druckplatten betreffen. Radiale Schlitze sollen die Behinderung der thermischen Dehnung verhindern und dadurch Spannungen reduzieren; die Werkstoffauswahl auf Basis der Thermoschockempfindlichkeit reduziert die plastische Verformung. Anhand einer kombinierten Simulation der Thermik und der Mechanik einer Druckplatte wird der Effekt dieser Ansätze an vier Varianten der Druckplatte überprüft. Experimentelle Untersuchungen an realen Prototypen der Druckplattenvarianten bestätigen die Ergebnisse der Simulation und weisen die Wirksamkeit der vorgeschlagenen Maßnahmen zur Reduzierung der plastischen Verformung nach.
Keywords: General Engineering; Bremsen; Bremsscheiben; thermoplastische Verformung

Damage modeling in the numerical simulation of mechanical joining processes - Otroshi, Mortaza

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

A Damage Model for Corrosion Fatigue Due to Hydrogen Embrittlement - Shi, Yuhao; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Material Modeling and Structural Mechanics)
Predicting the durability of components subjected to mechanical load under environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. The demand for precise predictions increases with the desire of lightweight design in transportation due to environmental protection. Corrosion with its manifold of mechanisms often occurs together with the production of hydrogen by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions often leading to early and unexpected failure. Until now, predictions are mostly based on costly experiments. Hence, a rational predictive model based on the fundamentals of electrochemistry and damage mechanics has to be developed in order to reduce the costs. In this work, a first model approach based on classical continuum damage mechanics is presented to couple both, the damage induced by the mechanical stress and the hydrogen embrittlement. An elaborated two-scale model based on the selfconsistent theory is applied to describe the mechanical damage due to fatigue. The electrochemical kinetics are elucidated through the Langmuir adsorption isotherm and the diffusion equation to consider the impact of hydrogen embrittlement on the fatigue. The modeling of the mechanism of hydrogen embrittlement defines the progress of damage accumulation due to the electrochemistry. The durability results like the S-N diagram show the influence of hydrogen embrittlement by varying, e.g. the fatigue frequency or the stress ratio.
Keywords: Hydrogen embrittlement; Fatigue; Continuum damage mechanics; Numerical simulation; Multi-field problem

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Can Machine Translation be a Reasonable Alternative for Multilingual Question Answering Systems over Knowledge Graphs? - Perevalov, Aleksandr; Both, Andreas; Diefenbach, Dennis; Ngonga Ngomo, Axel-Cyrille (WWW ’22: The ACM Web Conference 2022, Virtual Event, Lyon, France, April 25 - 29, 2022)

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (HT ’22: 33rd ACM Conference on Hypertext and Social Media, Barcelona, Spain, 28 June 2022- 1 July 2022)

Behavioral Economics for Human-in-the-Loop Control Systems Design: Overconfidence and the Hot Hand Fallacy - Protte, Marius; Fahr, Rene; Quevedo, Daniel E. (IEEE Control Systems)
Keywords: Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering; Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Development of a crash behaviour prediction method for resistance spot welded 3-steel sheet joints - Olfert, Viktoria; Meschut, Gerson; Hein, David; Schuster, Lilia; Sommer, Silke
The recent trend towards extensive electric mobility leads to a variety of new challenges for the engineering of future vehicle concepts. One particular challenge is the additional weight added to the vehicle by the battery, which stands in direct contrast to the existing customer expectation of a high driving range. The reduction of the total vehicle weight is driven by the extensive use of ultra-high-strength steels in thin sheet thicknesses in car body construction. Resistance spot welding is the dominant joining process in steel-intensive lightweight construction due to its high degree of automation, process reliability and the associated economic efficiency. In order to comply limitations of the space in the vehicle body and to ensure the most efficient use of materials in lightweight construction, joints are used that connect several sheets with a single spot weld. This leads to new challenges for the prediction of the load-bearing capacity and failure behaviour under crash loading. This paper presents a systematic characterisation of 3 sheet steel joints in order to find formulary, empirical relationships between the load-bearing capacity of the joint and the affecting parameters. Numerical simulations are carried out in order to clarify the causes of occurring phenomena in experiments. For this purpose, influencing variables such as joint strength, joint arrangement, sheet thickness, sheet strength, load type and load case on the load bearing capacity and failure behaviour are identified. Furthermore, the extent to which the behaviour of 2-sheet joints can be transferred to 3-sheet joints is investigated. A formulary correlation enables a quick and inexpensive estimates of the load-bearing capacity of 3-sheet metal connections. These models can be used for a computer-efficient simulation of components with three layered spot welded joints.

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Development of Simulation Based Assistant Systems for Automatic Process Monitoring and Derivation of Recommendations to Optimize a Profile Extrusion Line - Schöppner, Volker; Köllermeier, Jonas; Hiesgen, G.; Trippe, J.

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Global weak solutions and absorbing sets in a chemotaxis-Navier–Stokes system with prescribed signal concentration on the boundary - Black, Tobias; Winkler, Michael (Mathematical Models and Methods in Applied Sciences)
An initial-boundary value problem for a coupled chemotaxis-Navier–Stokes model with porous medium type diffusion is considered. Previous related literature has provided profound knowledge in cases when the system is augmented with no-flux/no-flux/no-slip boundary conditions for the density of cells, the chemical concentration and the fluid velocity field, respectively; in particular, available qualitative results strongly indicate that only trivial solution behavior can be expected on large time scales. In line with refined modeling approaches to oxygen evolution near fluid-air interfaces, this study now focuses on situations involving a fixed chemoattractant concentration on the boundary. Despite an apparent loss of mathematically favorable energy structures thereby induced, by means of an alternative variational approach a basic theory of global existence is developed in a natural framework of weak solvability. Beyond this, some additional qualitative information on the large time behavior of these solutions is derived by identifying a certain global relaxation property. Specifically, a second result asserts, within a suitable topological setting, the existence of a bounded set which eventually absorbs each individual of the obtained trajectories, and the diameter of which is bounded only by the physically relevant quantities of total population size and prescribed boundary concentration of the chemical signal.
Keywords: Applied Mathematics; Modeling and Simulation

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo